Publishing in English or Chinese: a qualitative analysis of Chinese researchers’ academic language choice - Jing Cui; Changbo Qiu; Zhigang Wang (Frontiers in Psychology, 2023)
Non-native language scholars often struggle to choose between English and their native language in scholarly publishing. This study aims to identify the mechanism by which journal attributes influence language choice by investigating the perspectives of 18 Chinese scholars through semi-structured interviews. Drawing on grounded theory, this study develops a model for how journal attributes influence researchers’ language preferences. We find that journal attributes influence researchers’ perceived value which, in turn, affects their particular language choice, with contextual factors playing a moderating role. By examining the motivations underlying Chinese scholars’ language choice, this study provides a critical understanding of the factors shaping their decision-making processes. These findings have significant implications for Chinese scholars, policymakers, and journal operators, shedding light on the issue of discrimination in academic publishing. Addressing these concerns is crucial for fostering a fair and inclusive academic environment.